2019
DOI: 10.1097/ajp.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Parental Report of Self and Child Worry During Acute Pain

Abstract: Objectives: To determine which variables predict parental post-vaccination pain ratings. It was hypothesized that after child behaviour, parental sensitivity and parental reports of worry would be the strongest predictors. Methods: Data for 215 parent-child dyads were analyzed from a longitudinal cohort at the preschool (4-to-5 years of age) vaccination. Preschoolers' pain behaviours 15 seconds, 1 minute-15 seconds, and 2 minutes-15 seconds after the painful immunization were observed and rated. Parental sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Similar findings were reported with the OUCH Cohort's preschooler wave. Mamedova et al 34 found that most variance in parent pain ratings was not predominantly based on preschoolers' pain behaviors. Only 28% of parent pain judgements were based on preschooler's pain behaviour.…”
Section: Lesson 4: Encouraging a Healthy Distrust Of Reports On Anoth...mentioning
confidence: 99%
“…Similar findings were reported with the OUCH Cohort's preschooler wave. Mamedova et al 34 found that most variance in parent pain ratings was not predominantly based on preschoolers' pain behaviors. Only 28% of parent pain judgements were based on preschooler's pain behaviour.…”
Section: Lesson 4: Encouraging a Healthy Distrust Of Reports On Anoth...mentioning
confidence: 99%